EFL Teachers’ Perceptions and Experiences in Implementing Differentiated Instruction (DI) in The Merdeka Curriculum at Vocational Schools in Riau Islands Province - Agustean, Nevi Santy; Sundari, Hanna; Puspitasari, Maya (IKIP Siliwangi, 2025)
The study addresses the challenges of implementing Differentiated Instruction (DI) in vocational schools in Indonesia, particularly in the Riau Islands. The objective is to examine how teachers adapt DI to students'' diverse needs and the impact of DI training, especially among the few Guru Penggerak-certified educators. This study utilizes a qualitative research design with a case study approach. Data were collected through questionnaires, semi-structured interviews, and classroom observations. Purposive sampling was used to select three teachers from different schools, focusing on their perceptions and practices related to DI within the Merdeka Curriculum framework. The study concludes that while Differentiated Instruction (DI) is being implemented effectively by English teachers within the Merdeka Curriculum, there are variations in its application. Teacher training is crucial in enhancing DI practices, but challenges remain in material access, school culture, and alignment with modern trends. Recommendations include expanding DI-focused professional development, improving resource availability, and fostering a more supportive school culture for DI integration.